2022
DOI: 10.3390/jcm11020470
|View full text |Cite
|
Sign up to set email alerts
|

XR (Extended Reality: Virtual Reality, Augmented Reality, Mixed Reality) Technology in Spine Medicine: Status Quo and Quo Vadis

Abstract: In recent years, with the rapid advancement and consumerization of virtual reality, augmented reality, mixed reality, and extended reality (XR) technology, the use of XR technology in spine medicine has also become increasingly popular. The rising use of XR technology in spine medicine has also been accelerated by the recent wave of digital transformation (i.e., case-specific three-dimensional medical images and holograms, wearable sensors, video cameras, fifth generation, artificial intelligence, and head-mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 140 publications
1
79
0
3
Order By: Relevance
“…This is perhaps a limitation of the current application; however, applications are being released that include holographic recognition of surgical instruments and holographic screens for other intraoperative digital technologies. Other technologies, such as video conferencing systems, have been shown to be valuable in remote surgical education across the globe, including broadcasting of surgical procedures [ 9 , 10 ]. This often requires the use of extensive operating theatre upgrades for catching different camera angles, additional microphones, and even a surgeon narrator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is perhaps a limitation of the current application; however, applications are being released that include holographic recognition of surgical instruments and holographic screens for other intraoperative digital technologies. Other technologies, such as video conferencing systems, have been shown to be valuable in remote surgical education across the globe, including broadcasting of surgical procedures [ 9 , 10 ]. This often requires the use of extensive operating theatre upgrades for catching different camera angles, additional microphones, and even a surgeon narrator.…”
Section: Discussionmentioning
confidence: 99%
“…Madani et al [ 9 ] noted limitations of such systems for open procedures given the limited mobility of the cameras, though they did suggest the ability to use head-mounted cameras may resolve these concerns. Morimoto et al [ 10 ] describe the use of “action cameras” to record surgery from the surgeon's perspective, but note that an ideal camera is not currently available. Though these recordings may perform well in educational settings, they do not allow real-time interaction from the surgeon's viewpoint intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, AR holds high capability for future concepts. In spinal neurosurgery, AR-assisted procedures have been applied especially for screw placement in combination with navigation or robot assistance within the last decade [ 12 , 23 , 35 ]. Phantom studies and cadaver simulations have also demonstrated promising applications of AR in cranial neurosurgery with techniques for cranial biopsy or accurate catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…Under VR technology, the real environment where the user is located can be any place with little interference. When the user wears the virtual device, all the environment perceived by the user is a virtual effect, which plays an important role in the user's body detection and observation [11]. Figure 1 shows the basic situation of VR technology.…”
Section: Research Theories and Methodsmentioning
confidence: 99%